EFeed-Hungers.com: Mitigating global hunger crisis using next generation technologies. Issue 2 (May 2018) - Sharma, Sugam; Shandilya, Ritu; Tim, U. Sunday; Wong, Johnny
Highlights: We conceived, conceptualized and constructed eFeed-Hungers.com to alleviate hunger. The eFeed-Hungers.com serves as an efficient bridge between waste food and needy. The eFeed-Hungers.com assists channeling of waste food to needful destinations. The eFeed-Hungers.com will be accessed and accepted at global scale. eFeed-Hungers.com is envisioned to be an organization working for hunger free world. Abstract: Hunger is a global crisis and impacting the world for a very long time. Significant efforts have been made in the past by various organizations employing various means to address this persisting problem. Despite this, it still remains far from being resolved. Recently, the United Nations has published a report on global hunger, which claims that the global food production is fairly enough to feed the entire world with a population of about 7.3 billion. However, a major quantity of the food grown is not channeled appropriately and effectively to reach the needy and thus gets wasted unfortunately. Using the advanced computer technologies, we devise and develop a web-based computational framework ( eFeed-Hungers.com ) that serves as a bridge between the food waste and the hunger to mitigate the hunger issue; the food waste is the excess, unused, edible food, which otherwise is destined to the dumpster unfortunately. The eFeed-Hungers.com encourages and assists the food waste donation announcements with the least minimal efforts with the best possible outreach. Through the eFeed-Hungers.com, the food donations are globally searchable by the needy, with enough additional information imparted for quick decisions making to fetch the appropriate donated food. The eFeed-Hungers.com is envisioned to be a fully functional organization eventually with global outreach.